Traditional Chinese medicine for irritable bowel syndrome: A protocol for meta-analysis. Issue 48 (25th November 2020) - Yao, Cheng-Jiao; Li, Yi-Lin; Pu, Meng-Jun; Luo, Li-Hong; Feng, Pei-Min
Abstract: Background: Irritable bowel syndrom (IBS) is a common functional gastrointestinal disorder which is characterized as recurrent abdominal pain, abdominal discomfort, and abnormal bowel habits such as diarrhea, constipation, both or alternate appear. Although IBS is not fatal, it seriously affects the patients' daily life and work. Western drug, such as antidiarrheals, gastrointestinal antispasmodic, often cannot get satisfying curative effects. However, the therapeutic effect of Traditional Chinese medicine (TCM) on IBS is very satisfactory which was shown in a large number of randomized controlled trials. Although TCM has been widely used in clinical practice, its relative effectiveness and safety have not been confirmed. Therefore, this study will use meta-analysis to verify the efficacy and safety of different types of TCM in the treatment of IBS. Methods: We search the China National Knowledge Infrastructure, Wanfang Database, Chinese Science and Technology Periodical Database, Chinese Biomedical Literature Database, Pubmed, Embase, Web of Science, and the Cochrane library for all randomized controlled trial of TCM for the treatment of IBS from their inception to Oct 15, 2020. Two authors will independently select studies, extract data based on predesigned inclusion and exclusion criteria. Methodological quality assessment and risk of bias will be assessed using Cochrane bias risk tool. All data analysis will be conducted using Revman5.3, WinBUGS 1.4.3, and Stata14.2 software. Results: This study will compare the different outcome indicators of various studies directly and indirectly, and provide a high-quality synthesis of effectiveness and safety of different TCM methods for patients with IBS. The main outcome indicators include effectiveness, remission rate (no drug symptoms), relapse rate, clinical absolute score, and relative score. Secondary outcome indicators included related adverse reactions and serum serotonin concentration. Conclusion: The conclusion of this systematic review will provide a high-quality evidence based on the efficacy and safety of different TCM treatment methods for IBS. Registration number: This study protocol has been funded through a protocol registry. The registry number is INPLASY2020100052